NEW RECORD OF THE MONOCLED COBRA Naja kaouthia Lesson, 1831 (SQUAMATA: ELAPIDAE) FROM SON LA PROVINCE, NORTHERN VIETNAM - Sy Tuong, Dinh; Trung Hieu, Pham; Thi Thuy Dung, Dinh; Quang Vinh, Luu (Journal of Forestry Science and Technology, 2021)
In Vietnam, the Monocled cobra Naja kaouthia is a poorly known species with few records from Quang Tri, Thua Thien-Hue, Lam Dong, Dong Nai, Ho Chi Minh City, Dak Lak and Kien Giang provinces. The species is diagnosed in morphology as follows: Large head; a cuneated scale between fourth and fifth infralabial; single preocular; postoculars 2 - 3; supralabials 7/7, the third & fourth entering orbit; 4 infralabials contact anterior chin shields; rounded hood with O-shaped marking. Body robust, cylindrical; scales smooth, mid-body scale rows 19 - 21 (usually 21); ventrals 164 - 197. Tail short, tapering; paired subcaudals 43 - 61. During recent herpetological survey in the karst forest of Van Ho District, Son La Province, Vietnam, a female specimen of the genus Naja was collected at an elevation of 800 m a.s.l. in a mixed habitat of the secondary karst forest and agricultural area. Based on morphological examination, our specimen is totally agreed with the Monocled cobra Naja kaouthia Lesson, 1831 description of Smith (1943), Das (2010), Chan-ard et al. (2015) and Vassilieva et al. (2016). Thus, the species is recorded for the first time from Son La Province. The species is listed in the Appendix II of CITES (2019) and Group IIB of the Vietnamese Governmental Decree No 06/2019/ND-CP.